How do Grocery Stores Create Industrial Economics in Surabaya: The Role of Competitive Strategy - Azis, Abdul; Merlinda, Santi; Dwiputri, Inayati Nuraini; Annisya, Annisya; Wahyuningsih, Rani Destia (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
Business competitiveness plays a crucial role in the future development of grocery stores. To sustain growth, grocery stores must be able to adapt and create changes that foster brand trust. Grocery stores primarily serve middle to lower-income consumers by offering essential goods. The expansion of grocery stores in Surabaya continues to rise, as evidenced by 1,504 stores across 31 districts. Dukuh Pakis contributes 3.72% to this total, with 32 active grocery stores. This study aims to assess the competitive readiness of grocery stores to adapt to consumer changes and establish brand trust. A quantitative approach was employed, focusing on the 32 active grocery stores in Dukuh Pakis District. The findings indicate that 15 grocery stores (47%) fall under Grade 3, 8 stores (25%) under Grade 2, and 9 stores (28%) under Grade 1. The competitiveness assessment, measured through four dimensions, yielded a score of 13.06787109, classifying grocery stores in Dukuh Pakis District as having a strong competitive position. Keywords: industrial economics, competitive strategy, grocery stores, Surabaya city